Oxford Research Encyclopedia of Education 2020
DOI: 10.1093/acrefore/9780190264093.013.932
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Students’ Assessment Feedback Skills Within Higher Education

Abstract: In higher education (HE) considerable attention is focused on the skills sets students need to meet the requirements of the fourth industrial revolution. The acquisition of high-level assessment feedback skills is fundamental to lifelong learning. HE has made significant investment in developing assessment feedback practices over the last 30 years; however, far less attention has been given to the development of inclusive agentic integrated assessment systems that promote student agency and autonomy in assessm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(46 citation statements)
references
References 78 publications
(121 reference statements)
1
45
0
Order By: Relevance
“…Student responses to open-ended questions also revealed that opportunities to triangulate feedback from their instructor, peers, and self-assessment in a formative process for learning inspired them to improve their course designs before final submission for summative assessment. These findings align with literature supporting the need for peer feedback activities to provide early opportunities for timely feedback from multiple sources 9…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Student responses to open-ended questions also revealed that opportunities to triangulate feedback from their instructor, peers, and self-assessment in a formative process for learning inspired them to improve their course designs before final submission for summative assessment. These findings align with literature supporting the need for peer feedback activities to provide early opportunities for timely feedback from multiple sources 9…”
Section: Discussionsupporting
confidence: 86%
“…These findings align with literature supporting the need for peer feedback activities to provide early opportunities for timely feedback from multiple sources. 9 The findings from this study lay the groundwork for intentional collaborative course designs and future study of how students perceive and respond to peer feedback in nurse education classrooms that include different cultural or national backgrounds. Instructional interventions should be aimed specifically at developing a growth mindset prepared for self-reflection and performance improvement in response to peer feedback from diverse colleagues.…”
Section: Discussionmentioning
confidence: 82%
“…Ultimately, exchange of high-quality peer feedback in well-designed peer review activities will support development of self-regulation in learning, deeper student engagement with performance standards, and effective collaboration in high-functioning teams. 9 The purpose of this study was to explore the factors that motivate and demotivate nursing students to provide supportive feedback to peers and identify pedagogical approaches to peer review instruction that support exchange of high-quality peer feedback. Two questions guided this study: (1) How do nursing students describe factors that motivate and demotivate them to provide supportive feedback to peers?…”
Section: Nurse Educatormentioning
confidence: 99%
“…Therefore, a deeper understanding of the motivating forces for students who transfer knowledge about peer feedback and apply peer-review skills in authentic contexts will help faculty plan educational opportunities that promote a strong sense of value for providing supportive peer feedback among all students. Ultimately, exchange of high-quality peer feedback in well-designed peer review activities will support development of self-regulation in learning, deeper student engagement with performance standards, and effective collaboration in high-functioning teams 9…”
mentioning
confidence: 99%
“…Group-based tasks require groups of learners to form a 'partnership' to resolve problems, realise outcomes, or create products. By integrating these salient aspectsa standard task or activity, small group learning, cooperative behaviour or positive interdependence, individual responsibility, and accountability (Johnson, 1991;Laal & Ghodsi, 2012;Le et al, 2018;OECD, 2013OECD, , 2017 collaborative learning has proven to generate numerous proximal (increased academic achievement and employability) and distal (increased workplace efficiency) benefits for undergraduates (Evans & Waring, 2020).…”
Section: Introductionmentioning
confidence: 99%